Tartas 1, Russische F öderation: Ausgrabungen in einer der größten prähistorischen Nekropolen Westsibiriens - Reinhold, Sabine; Nagler, Anatoli (e-Forschungsberichte des DAI, 2023)
The burial site of Tartas 1 in the Baraba forest steppe of Western Siberia is one of the most fascinating sites in Eurasia. Situated on a slight hill along a river bend, Tartas 1 and the opposite burial ground of Sopka 2 form the centre of a burial tradition lasting for more than 4000 years. Tartas 1 is excavated in a joint Russian-German project of the Eurasia department and the Institute of Archaeology and Ethnography of the Siberian Branch RAS since 2004. Meanwhile more than 650 burials have been excavated, together with more than thousand pits, which belong to ritual or domestic structures. The site is a focus of multidisciplinary investigation including ancient DNA studies, radiocarbon and bioarchaeological analytics.